Effect of Late-Onset Stroke Rehabilitation on Medical Morbidities and Functional Recovery: A Single-Center Observational Study - Sahoo, Pabitra Kumar; Nehal, Nehal (Curēus (Palo Alto, CA), 2022)
Background The concept of focused rehabilitative care and a dedicated rehabilitation setup is fairly less known among the people of developing countries. The main objective of the study is to assess the effect of late-onset stroke rehabilitation on its overall prognosis and to see whether and how the late initiation of rehabilitation would pose a significant effect on functional recovery and adverse medical outcomes Methods A single-center, prospective observational study was conducted in a tertiary rehabilitation center for a duration of one and a half years. The subjects admitted to the Department of Physical Medicine and Rehabilitation were divided into three groups with respect to the onset to admission interval (OAI). Patients who got admitted within 30 days (OAI≤ 30 days) were considered the early rehabilitation group. OAI between 31 and 150 days was the late rehabilitation group and OAI of 151 days or more was the very late rehabilitation group. Barthel Index (BI), Modified Rankin Score (MRS), and 6-minute walk test (6MWT) were used as functional outcome measures at admission and discharge from indoors. Results Maximum complications were observed in the late rehabilitation group, i.e. 2.75±2.74, with an overall mean of 2.02±2.04 (p=0.003). Functional recovery assessed using BI shows a significant difference between the early (35.79±8.86) and late (40.62±10.5) rehabilitation groups (p= 0.0005). 6MWT at discharge showed significant improvement in the early rehabilitation group (p=0.005). Conclusion Early onset of rehabilitation showed better functional recovery and fewer adverse medical outcomes in stroke patients. A longer length of hospital stay (LOHS), with a mean duration of 88 ±2 days was needed for patients with higher OAIs.